Strategi Keberlanjutan Pusat Kegiatan Belajar Masyarakat untuk Menunjang Sinergitas dengan Dunia Industri dalam Mewujudkan Ekonomi Hijau di Kabupaten Ketapang - Muhani, Urai; Diah, Januardi M.; S. Purba , Charlyna (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research was conducted in Ketapang Regency, West Kalimantan, focusing on the collaboration between SMK Negeri 1 Nanga Tayap and PT Bumitama Gunajaya Agro (PT. BGA) through the Community Learning Activity Center (PKBM) program. The program has been running for three years and provides equivalency education (Packages A, B, and C) for company employees and local communities, with most participants funded by the company as part of human resource development efforts. The initiative has received positive responses, with limited support from the Provincial Education Office. As Ketapang is one of Indonesia’s major palm oil production centers, the PKBM program is linked to green economy issues as part of a broader sustainable development agenda. This study uses a descriptive qualitative method, with data collected through interviews, documentation, and literature review. The analysis applies the Pentahelix collaboration model, involving academia, industry, government, community, and media. The findings indicate that PKBM effectively expands access to education, fosters environmental awareness, and builds cross-sector synergy to support green economy-based social transformation in plantation areas.